COMPLIANCE OF HYPERTENSION PATIENTS IN DOING SELF-CARE: A GROUNDED THEORY STUDY - Pius A. L. Berek; Yati Afiyanti (Program Studi Keperawatan, Universitas Timor, 2020)
Hypertensi as a one of non-communicable diseases is need of serious attention and dealt with